2016
DOI: 10.4049/jimmunol.1401545
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Controls TLR9 Trafficking to Phagosomes Containing β-1,3 Glucan

Abstract: Dectin-1 and TLR9 play distinct roles in the recognition and induction of innate immune responses to Aspergillus fumigatus and Candida albicans. Dectin-1 is a receptor for the major fungal cell wall carbohydrate β-1,3 glucan that induces inflammatory cytokines and controls phagosomal maturation through Syk activation. TLR9 is an endosomal Toll-like receptor that also modulates the inflammatory cytokine response to fungal pathogens. In this study, we demonstrate that β-1,3 glucan beads are sufficient to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…TLR9 is an endosomal TLR that modulates the inflammatory cytokine response to A. fumigatus (Bellocchio et al., ; Carvalho et al., ; Khan et al., ; Ramaprakash, Ito, Standiford, Kunkel, & Hogaboam, ). Phagosomal TLR9 expression is controlled by dectin‐1 (Khan et al., ) and is increased in neutrophils challenged with conidia and hyphae, and induction of TLR9 expression positively correlates with the induction of antifungal effector functions by these cells (Bellocchio et al., ). In a mouse model of fungal asthma, TLR9 −/− mice exhibited significantly lower airway hyper‐responsiveness after challenge with resting conidia compared to the TLR9 +/+ mice and A. fumigatus ‐sensitized TLR9 −/− mice exhibited pulmonary fungal growth up to 28 days after challenge with swollen conidia, an observation that was not found in A. fumigatus ‐sensitized TLR9 +/+ mice (Ramaprakash et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR9 is an endosomal TLR that modulates the inflammatory cytokine response to A. fumigatus (Bellocchio et al., ; Carvalho et al., ; Khan et al., ; Ramaprakash, Ito, Standiford, Kunkel, & Hogaboam, ). Phagosomal TLR9 expression is controlled by dectin‐1 (Khan et al., ) and is increased in neutrophils challenged with conidia and hyphae, and induction of TLR9 expression positively correlates with the induction of antifungal effector functions by these cells (Bellocchio et al., ). In a mouse model of fungal asthma, TLR9 −/− mice exhibited significantly lower airway hyper‐responsiveness after challenge with resting conidia compared to the TLR9 +/+ mice and A. fumigatus ‐sensitized TLR9 −/− mice exhibited pulmonary fungal growth up to 28 days after challenge with swollen conidia, an observation that was not found in A. fumigatus ‐sensitized TLR9 +/+ mice (Ramaprakash et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In allergic models of A. fumigatus exposure, dectin‐1 activation can lead to the induction of CCL17 (Lilly et al., ), and CCL17 affects CCL2 levels (Carpenter & Hogaboam, ). Dectin‐1 also controls trafficking of TL9 to A. fumigatus containing phagosomes (Khan et al., ), and TLR9 as well as TLR3 are involved in the production of IL‐10 (Carvalho et al., ; de Luca et al., ; Ramaprakash & Hogaboam, ). Previous studies have shown how SNPs in different genes such as dectin‐1 and CCL2 can have synergistic effects on susceptibility to aspergillosis (Sainz et al., ), and it may be that further analysis will prove that this is the case with SAFS.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of TLR9 is, in contrast to LC3 (Kyrmizi et al ., ), shown to be independent of the germination stage of conidia (Kasperkovitz et al ., ). Although more recent studies show that TLR9 recruitment to Aspergillus ‐containing phagosomes is dependent on Dectin‐1, phagocytosis of β‐glucan beads was already sufficient to traffic TLR9 to the phagosome (Khan et al ., ). In contrast to LAP, which requires the absence of both rodlet proteins ( ΔrodA ) and melanin ( Δalb1 ) (Akoumianaki et al ., ), localization of TLR9 to the phagosome does not require this removal (Kasperkovitz et al ., ).…”
Section: Novel Pathways Involved In Phagosome Maturationmentioning
confidence: 97%
“…A portion of TLR4/MD‐2 is colocalized with Rab11a in the endocytic recycling compartment and recruited to phagosomes in a manner dependent on Rab11a . TLR3, TLR7, TLR8, and TLR9 are recruited to phagosomes containing fungi or bacteria . Recruitment of endosomal TLRs to phagosomes seems to depend on activation of the tyrosine kinase Syk.…”
Section: Molecular Machinery Driving Endosomes/lysosomesmentioning
confidence: 99%